The Influence of Perceived Organizational Support, Work Motivation, and Work Discipline on Organizational Commitment - Herdi Ependi (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2026)
This study aims to analyze the influence of organizational support felt by work motivation, work motivation, and work discipline on the organizational commitment of employees of PT. Indo Muro Kencana, Central Kalimantan. The research uses a quantitative approach with a survey method. Data was collected through a closed questionnaire that was distributed to all employees in January 2025, with a census sampling technique so that 76 respondents were obtained. The dependent variable in this study is organizational commitment, while independent variables include perceived organizational support, work motivation, and work discipline. All variable indicators are measured using a five-point Likert scale. Data analysis was carried out using the help of SPSS software. The data quality test includes a validity test with Pearson correlation and a reliability test using Cronbach's Alpha. Furthermore, a classical assumption test was carried out which included normality, multicollinearity, and heteroscedasticity tests before hypothesis testing. Hypothesis testing was carried out using multiple linear regression analysis through t-test, F test, and determination coefficient (R²). The results of the study show that organizational support, work motivation, and work discipline that are felt in part have a positive and significant effect on organizational commitment. Work motivation is the most dominant variable. In addition, the results of the F test showed that the three independent variables simultaneously had a significant effect on organizational commitment. The value of the determination coefficient shows that the research model is able to explain the variation in organizational commitment quite strongly. These findings affirm the importance of organizational support, increased motivation, and consistent application of work discipline in building employee organizational commitment in a sustainable manner.